Correction: Injectable postoperative enzyme-responsive hydrogels for reversing temozolomide resistance and reducing local recurrence after glioma operation. (8th July 2020) - Zhao, Zongren; Shen, Jiawei; Zhang, Long; Wang, Lansheng; Xu, Haoyue; Han, Yuhan; Jia, Jun; Lu, Yang; Yu, Rutong; Liu, Hongmei
Abstract : Correction for 'Injectable postoperative enzyme-responsive hydrogels for reversing temozolomide resistance and reducing local recurrence after glioma operation' by Zongren Zhao et al., Biomater. Sci., 2020, DOI: ; 10.1039/d0bm00338g .